2014
DOI: 10.1186/s12939-014-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Do low-income coronary artery bypass surgery patients have equal opportunity to access excellent quality of care and enjoy good outcome in Taiwan?

Abstract: BackgroundEquity is an important issue in the healthcare research field. Many studies have focused on the relationship between patient characteristics and outcomes of care. These studies, however, have seldom examined whether patients’ characteristics affected their access to quality healthcare, which further affected the care outcome. The purposes of this study were to determine whether low-income coronary artery bypass surgery (CABG) patients receive healthcare services with poorer quality, and if such diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Several studies have proposed that health disparities will not improve without first improving quality of care [ 1 , 2 , 3 ]. Moreover, the findings of several other studies support the validity of this proposition [ 4 , 5 ].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Several studies have proposed that health disparities will not improve without first improving quality of care [ 1 , 2 , 3 ]. Moreover, the findings of several other studies support the validity of this proposition [ 4 , 5 ].…”
Section: Introductionsupporting
confidence: 71%
“…The k-means clustering algorithm is based on cluster analysis, is one type of data mining approach and is one of the most-used methods for partitioning clusters [ 17 ]. We have previously applied this approach in prior research work [ 4 , 5 ]. The hospital-level annual operation volume, risk-adjusted average length of stay and 30-day readmission rate during the previous year for each period was calculated, with this information used as the parameters for the k-means clustering algorithm, which subsequently classified the hospitals into two quality-based groups.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that people with lower socioeconomic levels receive inferior treatment 20. For example, a retrospective study in Taiwan found that low-income coronary artery bypass surgery was associated with poorer quality of services 22. Further research is needed to better understand the observed inequality in prescribing practices in the Arabian Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 32 ] Yu and his colleagues even applied it to define the quality of CABG care, and to explore the relationship among patient’s income status, the level of quality of care, and inpatient mortality. [ 33 ]…”
Section: Methodsmentioning
confidence: 99%